APPLYING SMALL GROUP DISCUSSION COMBINED WITH PICTURE TO IMPROVE WRITING SKILL OF THE EIGHTH-GRADE STUDENTS OF SMP CIPTA DHARMA DENPASAR - Rahmadonna Festa; I Komang Budiarta; I Gusti Agung Putri Wirastuti (Program Studi Pendidikan Bahasa Inggris Institut Pendidikan dan Bahasa Invada, 2023)
Students with proficient writing skills can articulate their thoughts, beliefs, knowledge, emotions, and experiences. Students should be familiar with paragraph arrangement and general structure. However, they continued to struggle with writing paragraphs, particularly descriptive paragraphs. In addition, they were unable to organize it in terms of general structures, coherence, and unity. The primary purpose of this study was to examine whether the writing skills of the eighth-grade students of SMP Cipta Dharma Denpasar might be enhanced through small group discussion combined with picture. This research employed a two-cycle classroom action research design. The relevant data were obtained using instruments, including paragraph construction tests and a structured questionnaire. Following a cyclical research procedure, it was determined that small group discussion combined with picture was suitable for enhancing the writing skills of the subjects. It was evident from the findings of the pre-test, post-test 1, and post-test 2 that their writing skills had improved significantly. In addition, it was supported by the structured questionnaire, which revealed positive responses to the technique. It may be inferred that the writing skills of the eighth-grade students of SMP Cipta Dharma Denpasar could be improved by small group discussion combined with picture